ANTISICKLING SCREENING OF THE UNRIPE FRUIT EXTRACTS OF Carica papaya (CARICACEAE) (International Journal of Food and Nutritional Sciences, 2022)
This research investigates the potential antisickling effects of Carica papaya unripe fruit extracts onHbSS red blood cells from non-crisis state sickle cell patients. Utilizing the soxhlet extraction methodwith various solvents, the dried unripe fruit of C.